Late Clinical Presentation of Inferior Vena Cava Deviation into the Left Atrium Following Atrial Septal Defect Repair in the Childhood - El-Sayed Ahmad, Ali; Kleine, Peter; Lehnert, Thomas; Moritz, Anton (The Thoracic and Cardiovascular Surgeon Reports, 2016)
A 19-year-old woman underwent ASD closure with patch in the childhood. Fifteen years later, she presented with severe cyanosis and dyspnea on exertion. Clinical diagnostics revealed a dislocation of the patch resulting in a right-to-left shunt (RLS) that was compensated in the past years by a recurrent ASD allowing a left-to-right shunt (LRS). The existing balance between interatrial shunts vanished by the growth of the patient leading to the clinical deterioration. After successful redo surgery, the patient was discharged home 8 days postoperatively.
Keywords: congenital heart disease; reoperation; imaging